Efforts to increase purchase decision through advertising creativity and product quality with brand image as intervening variable - Dewi, Sartika; Damarwulan, Liza Mumtazah; Ganika, Gerry (Enrichment : Journal of Management, 2024)
This study aims to examine the effect of advertising creativity and product quality on purchase decisions with brand image as an intervening variable. The research method used is quantitative with a descriptive approach. This research collects data based on questionnaires, literature studies and observations. The population in this study were Lux bath soap users in Cilegon City aged 17-35 years and a sample of 102 respondents using purposive sampling. The data analysis method used is Structural Equation Modeling (SEM) with the SmartPLS 4 analysis tool. This research has the results that advertising creativity has a positive and significant effect on purchase decisions, while product quality has positive and no significant effect on purchase decisions. Brand image can mediate the indirect influence of advertising creativity and product quality on purchasing decisions